Guidelines for Infection Control in the Urological Field, including Urinary Tract Management (revised second edition). (3rd September 2021) - Takahashi, Satoshi; Arakawa, Soichi; Ishikawa, Kiyohito; Kamei, Jun; Kobayashi, Kanao; Shigemura, Katsumi; Takahashi, Satoru; Hiyama, Yoshiki; Hamasuna, Ryoichi; Hayami, Hiroshi; Yazawa, Satoshi; Yasuda, Mitsuru; et al.
Abstract: The Committee for the Development of Guidelines for Infection Control in the Urological Field, including Urinary Tract Management of the Japanese Urological Association, together with its systematic review team and external reviewers, have prepared a set of practice guidelines, an abridged version of which is published herein. These guidelines cover the following topics: (i) foundations of infection control, standard precautions, route‐specific precautions, and occupational infection control (including vaccines); (ii) the relationship between urologists and infection control; (iii) infection control in urological wards and outpatient clinics; (iv) response to hepatitis B virus reactivation; (v) infection control in urological procedures and examinations; (vi) prevention of infections occurring in conjunction with medical procedures and examinations; (vii) responses to urinary tract tuberculosis and bacillus Calmette–Guérin; (viii) aseptic handling, cleaning, disinfection, and sterilization of urinary tract endoscopes (principles of endoscope manipulation, endoscope lumen cleaning, and disinfection); (ix) infection control in the operating room (principles of hand washing, preoperative rubbing methods, etc.); (x) prevention of needlestick and blood/bodily fluid exposure and response to accidental exposure; (xi) urinary catheter‐associated urinary tract infection and purple urinary bag syndrome; and (xii) urinary catheter‐associated urinary tract infections in conjunction with home care. In addressing these topics, the relevant medical literature was searched to the extent possible, and content was prepared for the purpose of providing useful information for clinical practice.